ON TEACHER’S COMPETENCES AND TEACHER’S SKILLS RAISING SYSTEM - Ivan S. Bolotin; Anastasiya A. Dorofeeva; Nina D. Sorokina (Высшее образование в России)
The article discusses the topical questions of formation of university teachers’ competences needed in conditions of education modernization. To solve this problem anappropriate system of university teachers’ training and retraining is required. Modern teacher must have a set of specific competences including such groups as functional, research and pedagogical, personal, and ethical. Meanwhile, the lecturer is in a situation where, on the one hand, the administration increases the load, and tightens the requirements, and on the other hand, the students exert pressure on teachers. In this situation universities should create the appropriate conditions to motivate teachers to improve their qualification, to update continuously learning methods.